Clinico-demographic Profile of Poisoning Cases Admitted in Intensive Care Unit of Bharatpur Hospital, A Tertiary Referral Center in Nepal - Paudyal, N.; Sapkota, K. (Kathmandu University Medical Journal, 2020)
Background Poisoning is a major cause of death in young adults. The epidemiological factors such as geography, occupation, literacy rate can influence the clinical presentation and outcome of the poisoning patients. Poisoning has a significant impact on the economic and social life of individuals. Objective The main objective of this study is an effort to evaluate the characteristic of poisoning cases and identify the reasons for Intensive Care Unit (ICU) admission. Method This was a prospective observational study at Bharatpur Hospital ICU over a period of one year. Demographic profiles, poison characteristics, types and reasons for poisoning, duration of hospital stay, and outcome of the patients were studied. Result A total of 156 patients were admitted with poisoning. Females were affected more than males with a ratio of F:M= 1.6:1. The age group that consumed poison the most was 16-25 years, and the mean age group of males was 35±14 years and 29±11 years respectively. The main cause of poisoning was conflicts/quarrel. Organophosphorus compound was the most common poisoning with 53% of total cases due to it. There were 07 cases of accidental poisoning secondary to mushroom poisoning. The mean duration of stay in ICU of these patients was 04 days. The total fatality rate due to poisoning was 07%. Conclusion The significant proportion of Intensive Care Unit admission was due to organophosphorus compounds. It was more common among females and young age groups. This calls for special health education on chemical safety among vulnerable people along with efficient supervision in regulatory controls on chemicals and its use.